The Influence of Trust, Customer Satisfaction, and Service Quality on Gen Z Loyalty to the Shopee Application - Afifa, Dias Ro'ul; Zulistiani, Zulistiani (Universitas Nusantara PGRI Kediri, 2024)
Research aim: This research aims to test and analyze the significant influence of the variables of trust, customer satisfaction and service quality on the Loyalty of the Generation Z Management Study Program, Universitas Nusantara PGRI Kediri on the Shopee Application partially or simultaneously. Design/Method/Approach: This research uses a quantitative approach and the technique used is associative causal. The population for this research is all customers who have made transactions on the Shopee application and the sample used in this research is 100 respondents who have made at least one transaction on the Shopee application and were analyzed using the multiple linear method. Research Findings: The results of this research are that the partial trust variable does not have a significant effect on loyalty. Customer satisfaction has a positive and significant effect on loyalty. Service quality has a positive and significant effect on loyalty. The variables of trust, customer satisfaction and service quality simultaneously have a significant effect on the loyalty of the Generation Z Management Study Program at Nusantara University PGRI Kediri on the Shopee Application. Theoretical contribution/Originality: research on the influence of trust, customer satisfaction and service quality on Gen Z loyalty in the Shopee application has several theoretical contributions that can provide a better understanding of the relationship between variables. Practitioner/Policy implications : This research provides practical implications for the Shopee Application in increasing customer satisfaction and loyalty Research limitations: limitations in this research were that it was conducted on a limited sample, so the results cannot be generalized to the entire generation z population.